1990
DOI: 10.1148/radiology.176.3.2389029
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the growth of renal neoplasms.

Abstract: A retrospective review of the imaging results of 11 patients with 13 solid renal parenchymal neoplasms was performed, allowing analysis of the linear growth rates of these tumors. The study sample included seven pathologically proved renal adenocarcinomas and six lesions that were indicative of a neoplasm radiologically (enhancing parenchymal mass on computed tomographic [CT] scans with documented interval growth), which were followed up for 2-7.8 years. Variable interval tumor growth was demonstrated in every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…Neumann et al [13] studied 26 RCC lesions in VHL patients over a 5-year follow-up and described a mean growth rate of 2.6 mm/year. The growth rate of tumours in VHL disease was compared to data provided by Birnbaum et al [31] , who showed 5.2 mm/ year for sporadic RCC. At the time, the authors concluded that tumour growth of RCC in VHL disease is slower than in sporadic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Neumann et al [13] studied 26 RCC lesions in VHL patients over a 5-year follow-up and described a mean growth rate of 2.6 mm/year. The growth rate of tumours in VHL disease was compared to data provided by Birnbaum et al [31] , who showed 5.2 mm/ year for sporadic RCC. At the time, the authors concluded that tumour growth of RCC in VHL disease is slower than in sporadic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although not an immediate threat to life, most RCCs tend to become significantly larger over time (i.e. grow to > 3 cm diameter) [19,20]. The mean 2-year survival in patients with metastatic RCC is 20% [5].…”
Section: Introductionmentioning
confidence: 99%
“…These data explain the clinical obser vation in cases of RCC in which, despite a non-surgical ap proach for various reasons, an almost proliferative arrest was noted at long-term follow-up [45]. On the other side unusual growth rates of low-stage were observed by imaging techni ques (CT, sonography) [46,47], A similiar correlation is found in other malignancies using the Ki-67 immunohistochemistry revealing a correlation between proliferation status and tumor grading, but no correlation with tumor stage [2,28,34,35]. Only a few authors have outlined the correlation of prolifera tive behavior of different malignancies and prognosis.…”
Section: Breast Cancermentioning
confidence: 69%